First magnetic resonance imaging-guided cardiac radioablation of sustained ventricular tachycardia. (November 2020) - Mayinger, Michael; Kovacs, Boldizsar; Tanadini-Lang, Stephanie; Ehrbar, Stefanie; Wilke, Lotte; Chamberlain, Madalyne; Moreira, Amanda; Weitkamp, Nienke; Brunckhorst, Corinna; Duru, Firat; Steffel, Jan; Breitenstein, Alexander; et al.
Highlights: First magnetic resonance image-guided cardiac radioablation (MRgRA) of sustained ventricular tachycardia. CIED MR safety and distortion artefact evaluation performed by pretreatment in silico testing. Successful real-time tracking and beam-gating despite interference by CIED distortion artefacts. MRgRA may have positive implications for the target volume definition and dose distribution. Abstract: Purpose: To report the feasibility of magnetic resonance imaging-guided cardiac single fraction radioablation (MRgRA) in a patient with dilated cardiomyopathy and recurrent sustained ventricular tachycardia (VT) leading to electrical storms (ES). Materials/methods: A workflow to perform Stereotactic Arrhythmia Radioablation (STAR) on a hybrid MR-Linac with real-time tracking and beam-gating was established. Challenges of the MRgRA approach included: (a) the safety of a non-MR compatible cardiac implantable electronic device (CIED) in the MR-Linac field, (b) artefacts caused by the CIED and (c) respiratory motion management with cine-tracking of the moving heart. The specific absorption rate and slew rate of the MR-Linac were within the specifications of a MR-conditional CIED. Phantom measurements showed CIED distortion artefacts of less than 1.5 mm. During MR simulation, tracking could be established on the upper liver to avoid interference with the moving heart and CIED extinction artefacts. Areas of anatomical scarring and critical substrate were identified using invasive three-dimensional electroanatomical mapping of the clinical VT during electrophysiological studies and cardiac MR imaging/computed tomography to build a volumetric target. Results: A 71-year-old male patient with non-ischemic dilated cardiomyopathy and recurrent therapy-refractory sustained VT with repetitive implantable cardioverter-defibrillator (ICD) shocks was treated with a single fraction of 25 Gy @85% isodose, cine-tracking time was 46 min, beam-on time 24 min. 24 h post intervention the patient developed an aggravation of the clinical VT and prolonged ES. VT ceased following high-dose dexamethasone administration after 48 h. After this point, the patient remained without any episodes of sustained ventricular tachyarrhythmia requiring ICD interventions until the last follow-up at three months. Conclusion: Real-time tracking and beam-gating were successfully applied in this first MRgRA to treat sustained VT.